2022
DOI: 10.1002/hsr2.1005
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum interleukin‐12 levels are associated with the pathophysiology of major depressive disorder: A case‐control study results

Abstract: Background and Aims Major depressive disorder (MDD) is the fourth biggest health‐related concern that dramatically impacts individuals' mental and physical health. Alteration of serum proinflammatory cytokine levels may take part in the development and progression of MDD. We aimed to explore and compare the role of interleukin‐12 (IL‐12) in MDD patients and healthy controls (HCs) and its involvement with the disease severity. Methods The present study included 85 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…80 Our previous studies also discovered that an imbalance of cytokines, antioxidants, and macro minerals might have an association with depression, which suggests that intake of these supplements might be beneficial for MDD patients. [81][82][83][84][85][86] The sample size and the data collection method were 2 of the primary advantages of this study. Previous researchers conducted their studies on a small scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Our previous studies also discovered that an imbalance of cytokines, antioxidants, and macro minerals might have an association with depression, which suggests that intake of these supplements might be beneficial for MDD patients. [81][82][83][84][85][86] The sample size and the data collection method were 2 of the primary advantages of this study. Previous researchers conducted their studies on a small scale.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory pathway mediates a connection between sickness behavior and clinical depression. 45 Rodent studies reported that the administration of pro-inflammatory cytokines induced depressive-like behaviors suggesting the association between depression and inflammation. 46 Elevated IL-2 levels cause the degradation of the tryptophan (TRP) enzyme, a precursor of serotonin production through the IDO pathway, and thereby lead to depression.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of MDD has increased during the COVID‐19 epidemic worldwide. 48 Several studies have been carried out in our lab to assess the possible role of cytokines in the development of MDD. 15 , 48 , 49 , 50 , 51 , 52 However, we found evidence in the literature that suggests IL‐1RA might be involved in MDD.…”
Section: Introductionmentioning
confidence: 99%
“…We need more research focused on developing specific biomarkers that might aid the precise assessment of MDD. The incidence rate of MDD has increased during the COVID‐19 epidemic worldwide 48 . Several studies have been carried out in our lab to assess the possible role of cytokines in the development of MDD 16,49‐53 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation